DIMENSI ONTOLOGIS, EPISTEMOLOGIS, DAN AKSIOLOGIS DALAM FILSAFAT PENDIDIKAN SEBAGAI FONDASI PEMBANGUNAN SUMBER DAYA MANUSIA - Shinta Anugrah Ikhtiarini; Amin Yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Education plays a fundamental role in shaping human resources (HR) that are qualified, ethical, and competitive amid global challenges. This study aims to analyze the roles of the ontological, epistemological, and axiological dimensions in the philosophy of education as the conceptual foundation for holistic human resource development. The research employs a qualitative-descriptive method through a literature review approach, examining various philosophical theories of education, particularly the humanistic theory proposed by Abraham Maslow and Carl Rogers. The findings reveal that the ontological dimension explains the nature of humans as rational, social, and spiritual beings who must be developed comprehensively; the epistemological dimension directs the process of acquiring knowledge through critical, reflective, and scientific thinking; while the axiological dimension determines the moral and ethical values that guide education toward humanity and social responsibility. The integration of these three dimensions forms an educational system that balances intellectual, emotional, and spiritual intelligence. In conclusion, the consistent application of these philosophical dimensions in education will produce human resources who are not only academically competent but also possess strong character, high ethical standards, and adaptive capabilities to meet the nation’s development needs.